A population-based cohort of adults with asthma: mortality and participation in a long-term follow-up. Issue 1 (1st January 2017) - Backman, Helena; Hedman, Linnea; Stridsman, Caroline; Jansson, Sven-Arne; Lindberg, Anne; Lundbäck, Bo; Rönmark, Eva
ABSTRACT: Background and objective : Asthma is a major public health concern. The aim of this study was to characterize a large population-based cohort of adults with asthma, and to study factors associated with all-cause mortality and non-participation in a long-term follow-up. Design : Random and stratified samples from five population-based cohorts were clinically examined during 1986–2001, and all subjects with asthma were included in the study ( n  = 2055, age 19–72 years, 55% women). Independent associations between different risk factors and (i) mortality and (ii) non-participation in a clinical follow-up in 2012–2014 were estimated. Results : In 1986–2001, 95% reported any wheeze and/or attacks of shortness of breath in the past 12 months, and/or asthma medication use. Over the up to 28 years of follow-up time, the cumulative mortality was 22.7%. Male gender, current smoking, and lower forced expiratory volume in 1 sec of predicted (FEV1 % of predicted) were independent risk factors for mortality, while obesity was associated with non-participation in the follow-up. Older ages, ischemic heart disease, and low socioeconomic status were associated with both mortality and non-participation. Conclusions : The risk factors associated with mortality in this adult population-based asthma cohort were similar to those commonly identified in general population samples, i.e. male gender, current smoking, and lower FEV1 % of predicted, while obesity was associated with non-participation in a long-term follow-up. Ischemic heart disease, low socioeconomic status, and older ages were associated with both mortality and non-participation.